Music in Puerto Rico : a reader's anthology - Thompson, Donald, 1928-2010 (Scarecrow Press, 2002)
Thompson's book provides a glimpse into a society in which cultures intersect and in which magic was born in the form of the popular salsa. Musicians, musicologists, historians, students of Hispanic culture, and anyone interested in the musical foundations of Puerto Rican life will fund Music in Puerto Rico a valuable resource.